2005
DOI: 10.1158/0008-5472.can-04-2484
|View full text |Cite
|
Sign up to set email alerts
|

SKI-606, a Src/Abl Inhibitor withIn vivoActivity in Colon Tumor Xenograft Models

Abstract: Src up-regulation is a common event in human cancers. In colorectal cancer, increased Src levels are an indicator of poor prognosis, and progression to metastatic disease is associated with substantial increases in Src activity. Therefore, we examined the activity of SKI-606, a potent inhibitor of Src and Abl kinases, against colon tumor lines in vitro and in s.c. tumor xenograft models. SKI-606 inhibited Src autophosphorylation with an IC 50 of f0.25 Mmol/L in HT29 cells. Phosphorylation of Tyr 925 of focal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 44 publications
8
132
0
1
Order By: Relevance
“…1B). This is consistent with previously published studies of bosutinib in colorectal xenografts (24) and breast xenografts (25) as well as other Src inhibitors in pancreas cancer mouse models (14).…”
Section: Effects Of Bosutinib Administration On Xenograftssupporting
confidence: 93%
“…1B). This is consistent with previously published studies of bosutinib in colorectal xenografts (24) and breast xenografts (25) as well as other Src inhibitors in pancreas cancer mouse models (14).…”
Section: Effects Of Bosutinib Administration On Xenograftssupporting
confidence: 93%
“…QGP-1 show high levels of Src family activity in comparison with several cancer cell lines of different origins. Interestingly, Src activity in QGP-1 was Endocrine-Related Cancer (2007) 14 111-124 www.endocrinology-journals.org comparable with Colo205, a colon cancer cell line frequently used for studies on the role of Src in neoplastic cells (Golas et al 2005).…”
Section: Discussionmentioning
confidence: 86%
“…We observed that QGP-1 cells display very high levels of Src activity, as elevated as that of Colo205 (Fig. 1B), a colon cancer cell line that is frequently used to study the role of up-regulation of Src in cancer cells (Golas et al 2005). Although lower than in QGP-1, the activity of Src in CM cells was comparable with that of MCF-7, a breast cancer cell line in which Src is required for cell proliferation and invasiveness (Castoria et al 2001).…”
Section: Expression Of Src Family Kinases In Pancreatic Endocrine Canmentioning
confidence: 87%
“…We and others have recently identified a role for Src kinase in acquired endocrine resistance in vitro [11,19], where it may regulate both proliferative and invasive responses in such cells. Data is emerging which reveals Src kinase as a novel tumour target, where its inhibition is effective at suppressing proliferation and/or metastatic events in a wide range of tumour types including CML [30,31], colon tumours [32,33] and pancreatic cancer [34,35]. Further studies [36,37] also provide compelling evidence that targeting Src may be of value in combination with existing chemotherapy to provide an augmented antitumour response.…”
Section: Discussionmentioning
confidence: 99%